PERLINDUNGAN HUKUM TERHADAP HAK ANAK YANG MENJADI TENAGA KERJA MIGRAN INDONESIA DI NEGARA LAIN - Anthony Wirasasmita, Michael; Tuni Cakabawa Landra, Putu; Eka Wisanjaya, I Gede Pasek (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
Protection on the rights of migrant children workers are basically available in various national and international rules, although many countries have ratified these conventions and has had national laws on the protection of children, there are still many violations on the rights of children that become migrant workers. The purpose of this writing is to know the international regulation for the children that became Indonesian migrant workers and then to find out what the Indonesia’s responsibility in protecting the rights of children who become the migrant worker. To analyze the problem in this study, a normative research methods has been used with the type of legal facts approach as well the as approach of legislation and international documents, and also the legal concept analysis approach.International arrangements that have been issued in order to regulate and protect the rights of a child of migrant workers are the Universal Declaration of Human Rights (1948), Convention on the Rights of the Child (1989), Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (1990), ILO Convention No. 138 on the Minimum Age Convention (1973), and ILO Convention No. 182 on the Worst Forms of Child Labour (1999). Afterward in the case of Indonesia's commitment in protecting the children of migrant workers, Indonesian liability are based on the humanitarian principles enshrined in Pancasila and the 1945 Constitution
Keywords: Migrant Workers, Rights of the Child, Legal Protection and International Convention